2012
DOI: 10.1159/000343954
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is an Independent Determinant of Ischemia-Modified Albumin

Abstract: Objective: We have measured ischemia-modified albumin (IMA), total antioxidant status (TAS), total oxidant status (TOS) and high-sensitivity C-reactive protein (hsCRP) levels in obese and normal-weight subjects to investigate if IMA can be used as a biomarker of oxidative stress and inflammation and if IMA was an independent determinant of obesity or not. Methods: The study was performed on 92 obese subjects (20 male, 72 female) aged 38 ± 11 years and 78 normal-weight controls (19 male, 59 female) aged 37 ± 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
1
12
0
2
Order By: Relevance
“…Ischaemia‐modified albumin (IMA) is a relatively new biomarker which is under research in several ischaemic and/or hypoxic conditions . In a recent study performed in the obese subjects compared to the normal‐weight controls, IMA and TOS were found to be elevated, whereas TAC significantly decreased and BMI was reported to be as an independent determinant for IMA .…”
Section: Discussionmentioning
confidence: 99%
“…Ischaemia‐modified albumin (IMA) is a relatively new biomarker which is under research in several ischaemic and/or hypoxic conditions . In a recent study performed in the obese subjects compared to the normal‐weight controls, IMA and TOS were found to be elevated, whereas TAC significantly decreased and BMI was reported to be as an independent determinant for IMA .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, elevated levels of IMA are thought to be associated with several diseases based on oxidative stress [57]. The cardiovascular risk factors and IMA are reported to increase in obesity [8, 9], metabolic syndrome [10], type 2 diabetes mellitus (DM) [11], and hypercholesterolemia [12]. …”
Section: Introductionmentioning
confidence: 99%
“…In another report, it was revealed that patients with hypertension had elevated IMA levels [50]. Also, it was reported that obesity caused increase in IMA levels indicating risk of ischemia in obese people [51]. In a study, higher levels of IMA were determined in patients who experience seizure, and it was reported that it could be used for differentiation of seizures [52].…”
Section: Study (Number Of Patients) [Reference Number] Usefulmentioning
confidence: 99%